Effects of soaking in glycerol and conventional solvents on the grinding of Kempas Wood (Koompassia malaccensis) - Poh, Lee Loh; Noor Azlina Abdul Ghani,; Nabilah Suhaili,; Zetty Shafiqa Othman,; Muhammad Rahimi Yusop,; Rizafizah Othaman,; Nur Hasyareeda Hassan, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Glycerol, the main by-product in biodiesel manufacturing, is a useful and environment-friendly solvent for many organic and inorganic substrates. This study investigates the effects of soaking using glycerol, silicone oil, dimethyl sulfoxide (DMSO) and Organosolv (1:1 water: ethanol) on energy consumption in the process of grinding kempas wood and on the particle size of ground kempas. Kempas wood chips were soaked in various solvents at 90°C for 1 h. The structural characterisation of untreated and treated kempas was analysed using CHNS, ATR-FTIR and XRD. Meanwhile, the grinding energy was calculated based on power per unit time while particle size was analysed using nested column sieves. Glycerol has high stability, good compatibility with other chemicals and is environmentally friendly. Glycerol-soaked kempas consumed less energy which led to energy saving of up to 0.015 W h and exhibited the smallest average particle size (263 μm) close to that of untreated kempas due to glycerol lubricating properties. Therefore, glycerol can be used as an alternative to conventional solvents in reducing the grinding energy consumption and particle size of lignocellulosic biomass.